Il Romano Pontefice Vicarius Christi (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Il tema – 2. Le fonti scritturistiche – 3. L’origine del titolo – 4. La moderna ecclesiologia - 5. Una speciale potestà vicaria.Roman Pontiff “Vicarius Christi”ABSTRACT: The papal title of Vicarius Christi, in recent ecclesiology, is no more exclusive than the Roman Pontiff, but belongs to each diocesan bishop, as specified in Council documents and in the latest codifications; each bishop holds his own particular church as Vicarius Christi with the powers that the law confers on him. Different is the exclusive power of the Roman Pontiff, who, by virtue of the Petrine office, which is proper to him, according to Catholic theology, has a true vicarious potestas, which allows him to derogate from positive divine law on the subject of indissolubility of marriage, dissolving marriages ratified and not consummated.